Assessment of the Learning Curve for Virtual Surgical Planning in Orbital Fractures. Issue 3 (September 2020) - Hsieh, Tsung-yen; Said, Mena; Dedhia, Raj D.; Timbang, Mary Roz; Steele, Toby O.; Strong, Edward Bradley
Virtual surgical planning (VSP) is becoming more widely used in maxillofacial reconstruction and can be surgeon-based or industry-based . Surgeon-based models require software training but allow surgeon autonomy. We evaluate the learning curve for VSP through a prospective cohort study in which planning times and accuracy of 7 otolaryngology residents with no prior VSP experience were compared to that of a proficient user after a single training protocol and 6 planning sessions for orbital fractures. The average planning time for the first session was 21 minutes 41 seconds ± 6 minutes 11 seconds with an average maximum deviation of 2.5 ± 0.8 mm in the lateral orbit and 2.3 ± 0.6 mm in the superior orbit. The average planning time for the last session was 13 minutes 5 seconds ± 10 minutes and 7 seconds with an average maximum deviation of 1.4 ± 0.5 mm in the lateral orbit and 1.3 ± 0.4 mm in the superior orbit. Novice users reduced planning time by 40% and decreased maximum deviation of plans by 44% and 43% in the lateral and superior orbits, respectively, approaching that of the proficient user. Virtual surgical planning has a quick learning curve and may be incorporated into surgical training.